Study and housekeeping - Coburn, Gertrude (My University, 1891)
Introduction: Among the questions that come to the busy, happy, sometimes heedless school-girl when, whether as preparatory student or more thoughtful graduate, she drops rules and ologies and smetries long enough to question of herself and her work “whither” and “why”, is one that was suggested when she finished the common school course and talked of going away to college. Devoted parents converse long before they finally decide that she can go. To give her up for four long years is hard. To send her away among strange people and new influences where home ties may be weakened and home-training defeated by the novel and charming life, is harder. But she must have more education than home schools can offer, and believing what the training of a college course will make her a better woman for her woman’s work, wherever, whatever it be, they prepare to send her away; and she, timid, hopeful, thoughtful awaits the eventful week when her new life and her college education will begin.
Citation: Coburn, Gertrude. Study and housekeeping. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Home economics; Housekeeping; School Girl; Theses; Manuscripts (documents)